PEMANFAATAN DAUN JATI DAN DAUN MANGGA SEBAGAI SUMBER PEWARNA ALAMI UNTUK KAIN PADA PENGRAJIN TENUN LOMBOK BERBASIS GREEN TEKNOLOGI - Kurniawidi, Dian W.; Ardianto, Teguh; Alaa', Siti; Alhadi, Kasnawi; Dewi, Diah L.; S., RR. Delima; Rahayu, Susi (Universitas Mataram, 2024)
The Mandalika Central Lombok Special Economic Zone (SEZ) is one of the world-class national priority tourist destinations. However, until now there has been no branding of the village's superior woven products that can contribute significantly to the Mandalika SEZ. So it is important to carry out this service activity, to give birth to entrepreneurial pioneer weaving craftsmen towards